The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1126/science.8383878
|View full text |Cite
|
Sign up to set email alerts
|

Sea Urchin Egg Receptor for Sperm: Sequence Similarity of Binding Domain and hsp70

Abstract: Fertilization depends on cell surface recognition proteins that interact and thereby mediate binding and subsequent fusion of the sperm and egg. Overlapping complementary DNA's encoding the egg plasma membrane receptor for sperm from the sea urchin Strongylocentrotus purpuratus were cloned and sequenced. Analysis of the deduced primary structure suggests that the receptor is a transmembrane protein with a short cytoplasmic domain. This domain showed no sequence similarity to known protein sequences. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 52 publications
(36 reference statements)
3
79
0
Order By: Relevance
“…There are two current hypotheses as to how the spermatozoon triggers meiotic progression in the quiescent oocyte. The first suggests that a soluble factor in the spermatozoon released into the egg cytoplasm following gamete fusion is the primary trigger [98][99][100][101], while the contrasting idea favors an externally located receptor mechanism involving G-protein [102] or tyrosine kinase [103]. Microinjection of cytosolic sperm extracts into hamster oocytes stimulated a series of Ca 2+ increases and mimic fertilization [101] and the factor has recently been identified as an oligomer with a Mr 33K subunit [104].…”
Section: Oocyte Activationmentioning
confidence: 99%
“…There are two current hypotheses as to how the spermatozoon triggers meiotic progression in the quiescent oocyte. The first suggests that a soluble factor in the spermatozoon released into the egg cytoplasm following gamete fusion is the primary trigger [98][99][100][101], while the contrasting idea favors an externally located receptor mechanism involving G-protein [102] or tyrosine kinase [103]. Microinjection of cytosolic sperm extracts into hamster oocytes stimulated a series of Ca 2+ increases and mimic fertilization [101] and the factor has recently been identified as an oligomer with a Mr 33K subunit [104].…”
Section: Oocyte Activationmentioning
confidence: 99%
“…Disruption of the ssel gene results in slow-growing cells at any temperature, suggesting an important role under normal conditions [10]. The most distant member of the group, a sea urchin sperm receptor, is located on the egg surface and interacts with the sperm protein, bindin [12]. Since the putative ATP-binding domain of HSP91 starts right from the N-terminus, the protein probably has a cytoplasmic or nuclear location.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our knowledge of HSP70s as a highly conserved group of proteins has been challenged by the isolation of two yeast HSP70 genes, ssel an sse2 [10] and the characterization of several animal cDNAs coding for high-molecular weight (HMW) heat shock-inducible proteins (90-110 kDa) with homology to HSP70s [11][12][13]. Since these proteins have several common features and low homology to the other HSP70s, they were proposed to represent a new HSP110/SSE1 subfamily of HSP70-related proteins [11].…”
Section: Introductionmentioning
confidence: 99%
“…The recombinant protein designated 45A represents a major portion of the N-terminal domain of the egg receptor for sperm (11,18). mAbs RS107 and RS132, which were prepared against the glutathione S-transferase-45A fusion protein (19) and protein A agarose were used for both immunoprecipitation and purification of the receptor.…”
Section: Methodsmentioning
confidence: 99%
“…Following early work in which a high molecular weight glycoprotein on the egg cell surface was implicated as a receptor for sperm (5)(6)(7), it was shown that Pronase-generated glycopeptides prepared from this crude receptor preparation inhibited fertilization, but without species specificity (8,9). Later, a cell surface glycoprotein with a molecular mass of 350 kDa was identified as the egg receptor in Strongylocentrotus purpuratus (10,11). This molecule, as well as a 70-kDa extracellular fragment generated by lysyl endoproteinase C digestion of intact eggs, were shown to contain sugars typical of both N-and O-linked oligosaccharides, as well as sulfate (10,12).…”
mentioning
confidence: 99%